Physical therapy in a patient with post-encephalitis tetra-paresis: a case report - Mahayati, Dewi Suci; Aryudha, Teja (International Journal of Research in Medical Sciences, 2022)
The purpose of the rehabilitation program is to improve motor skills, coordination, mobilization and other existing disorders to achieve independence in daily living (ADL). Physical therapy as part of the rehabilitation program can provide core stability exercises, facilitation and stimulation of motion of the upper and lower extremities, balance exercises and mobilization exercises, as well as strengthening exercises with facilitation and active stimulation techniques and using the patient’s body weight as a training burden. Strengthening exercise can reduce spasticity by strengthening the antagonist muscles. After six months of the rehabilitation program, manual muscle testing (MMT) was evaluated for the right upper extremity 3/5, left upper extremity 5/5, right lower extremity 1/5, left lower extremity 2/5. Ashworth scale right upper extremity 1/4, right lower extremity 2/4, and left lower extremity 1/4. Clonus is reduced, the patient can stand with maximum support without clonus for 10 minutes. Trunk impairment scale 12/23 and Barthel index 65/100. Mobilization of the patient is being able to sit with minimal assistance, namely stabilization in the pelvis, sitting to standing with moderate support, which is supported at the knee bilaterally, and standing with support at the knee and pelvic for 10 minutes. This case report concludes that although physiotherapy is done late with strengthening exercise and core stability strengthening techniques, it can improve motor skills, which in turn will increase the patient’s independence in carrying out functional activities and ADLs.